Generative contexts: generating value between community and educational settings - Lyles, Dan; Lachney, Michael; Foster, Ellen; Zatz, Zoe (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
As educators and researchers, the authors of this paper participated, at different points in time, in a National Science Foundation funded research program to place culturally responsive education into generative justice frameworks. We discovered that the mechanisms to create generative contexts—contexts where value can possibly be returned to the community where the people generating that value live and work—in-school, after-school, and not-school were not uniform and required individual attention and care. One can think of generative contexts as the educational preconditions for generative justice. We aim to show how generative contexts are crucial to understanding a larger theory of generative justice. To do this we provide three examples of generative contexts. First is a generative context in-school, where a technology teacher brought a community hairstylist into her classroom to help teach computer programming through cornrow braiding; a skill relevant to her African American students. Next is a generative context after-school where a student demonstrates soldering skills that she learned from family members. The third is a not-school “E-Waste to Makerspace” workshop where students created garden-technology designs for low-income communities.